UJI TOKSISITAS FRAKSI EKSTRAK ETIL ASETAT DAUN KAPULAGA (Amomum Compactum Soland) TEHADAP LARVA UDANG (Artemia salina LEACH) DENGAN MENGGUNAKAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Faridha Yenny Nonci; Nurshalati Tahar; Mulyanti Mulyanti (Universitas Islam Negeri Alauddin Makassar, 2017)
A researched has been done about Toxicity Test Fraction of Ethyl Acetat Extract Kapulaga leaves (Amomum Compactum Soland) against larvae of Artemia Salina Leach by Brine Shrimp Lethality Test (BSLT) Method. This research aimed do determine the effect of the toxicity of extractsand fractions result of Kapulaga leaves (Amomum Compactum Soland) by Brine Shrimp Lethality Test Method against larvae of Artemia salina Leach. The research begins with the selection of the sample, the sample drying and extraction by maceration using solvent ethanol 96%. Extract concentrated by rotary evaporator. The extract obtained further partitioned in advance using the ethyl solvent and later obtained ethyl soluble extract and ethyl insoluble extracts. Then extract the ethanol, soluble ethyl extract and insoluble ethyl extract toxicity first tested with the method of Brine Shrimp Lethality Test. The results showed extracts have high levels of toxic substances against larvae of Artemia salina Leach with LC50 values of 93,32 μg/ml. Sample were fractionated on a column of liquid chromatography in vacuo to give five fractions, namely the combined fractions A, B, C, D and E. Each fraction was tested for toxicity and fraction D has achieved results that have high toxic levels the other fraction compared with LC50 values of 74,13 μg / ml. Part of the identification results showed the presence of steroids, flavonoids and compounds of the class of phenol.